An MRI-visible immunoadjuvant based on hollow Gd2O3 nanospheres for cancer immunotherapy. Issue 59 (3rd July 2020) - Li, Xia; Wang, Xiupeng; Ito, Atsuo
Abstract : An MRI-visible immunoadjuvant based on hollow Gd2 O3 nanospheres significantly promotes the cellular uptake of a tumor antigen by antigen presenting cells, exhibits pH-dependent alteration of the MR signal intensity and markedly enhances the antitumor immunity. Abstract : Hollow Gd2 O3 nanospheres significantly promote the cellular uptake of a tumor antigen by antigen presenting cells, exhibit pH-dependent alteration of the MR signal intensity and markedly enhance the antitumor immunity. Hollow Gd2 O3 nanospheres are promising as magnetic resonance imaging (MRI)-visible cancer immunoadjuvants for cancer immunotherapy.